Service Distribution Channel in The Automotive Industry: The Case of Selective Distribution of a Given Car Brand in Poland - Janusz ZĄBEK (Communications of International Proceedings, 2022)
Placing a technical product on the market means that it must be maintained. Operation means performing activities that prepare the product for use and activities that result from using the product. For this reason, service distribution channels play an important role in the processes of delivering branded products. The overall aim of the article is to get to know the distribution channel of the services that are provided as part of the dealer network's activities. The main goal of the article is to identify the properties and characteristics of the channel that enables the distribution of services of a selected car brand. As a result of the structure research, the existence of four sets of properties and characteristics of the authorized service distribution channel was identified. A core set is a set of properties and characteristics derived from national and EU regulations. The next set is a set of properties and characteristics related to the requirements of the brand owner. The next set, the flow operating set, is a set of properties and characteristics related to the flow of information, materials, and technical solutions. The last set of properties and characteristics is the operational set of service activities. It denotes the properties and features that determine the performance of repair activities for a given car brand. Knowledge of the properties of the service distribution channel will enable the improvement of the structure of the branded products distribution channel. Finding better and better solutions will facilitate the distribution of new services and technologies.
Keywords: Marketing Channels; Service Distribution; Dealerships Network; Poland